The Well-Recognized Ability of Melatonin to Potentiate an Equilibrated Immune Response Calls for an Urgent Study about Its Use as an Adjuvant in Anti-SARS-CoV-2 Vaccines - Georges Maestroni (Vaccine Research, 2020)
Vaccines are a major weapon to control the present COVID-19 pandemic. To achieve this goal, vaccines should confer a robust and long-lasting immunity against SARS-Cov-2. Breakthrough infections and waning immunity are currently observed in patients that recovered from COVID-19 as well as in the vaccinated people. Therefore, a highly effective vaccine is needed to control the present and future outbreaks. Exogenous N-acetyl-5-methoxy-tryptamine or melatonin (MLT) is well known to potentiate an effective and equilibrated immune response in a variety of situation including viral and bacterial infections and vaccines against different microbial and cancer antigens. In regard to anti-SARS-Cov-2 vaccines, beside stimulating specific IgG production as well as specific CD4+ and CD8+ T cells, exogenous MLT might also enhance specific IgA and secretory IgA in the mucosae; hence, preventing the re-infection and/or asymptomatic transmission of the virus. Thus, a study is urgently proposed to evaluate the effects of MLT administration either before or after vaccination against SARS-Cov-2 to evaluate its effect on strength, quality and duration of the immunity. Las but not least, due to its powerful antioxidant and anti-inflammatory properties, MLT administration might minimize the occurrence of adverse events after the vaccination.